Pola Internalisasi Nilai-nilai Moderasi Beragama untuk menangkal Paham Radikal di Kalangan Mahasiswa - Sutarto Sutarto (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This qualitative research with a phenomenological approach aims to explore the pattern of internalizing the values of religious moderation to prevent the development of radical understanding among students. The research informants comprised 10 academic leaders with strategic positions as policymakers and 13 lecturers who teach religious subjects at IAIN Curup. Data collection techniques used semi-structured interviews and the Miles and Huberman analysis model. Checking the validity of the data is done by extending the interview and triangulation of sources. The results of the study show that the internalization of religious moderation values to prevent the development of radical understanding among students is carried out by inserting religious moderation values into courses, internalizing religious moderation values through the learning process, integrating religious moderation values through various student activities, internalization of the values of religious moderation through field practice, community service and special programs.